Therapeutic activities of artemesia Herba-Alba and Rosmarinus officinalis against microbial infection: a review - Osman, Abdinasir Yusuf; Mohamed Ali, Fathy; Nordin, Muhammad Luqman; Arshad, Mohd Mokhtar; Shaari, Rumaizi; Abu Hassan, Zainal Abidin; Ibrahim, Nazlina (2017)
Natural products are still major potential sources of innovative therapeutic agents for various conditions, including infectious diseases as they represent an unmet source of chemical diversity. This study was conducted to determine the anti-trypanosomal properties of Artemisia herba-alba and Rosmarinus officinalis in vivo settings. We have reviewed previous studies in the literature, which support the therapeutic activity of these plants and the data suggest that A. herba-alba as well as R. officinalis have anti-trypanosomal activites, and reinforce the use of this plant as an alternative remedy for microbial infection in traditional medicine.